Gender in non- ST elevation myocardial infarction and unstable angina: is there any equality?. (25th November 2020) - Lopes, J; Saleiro, C; Campos, D; Sousa, J; Puga, L; Gomes, A; Ribeiro, J; Lourenco, C; Silva, J; Goncalves, L
Abstract: Background: Historically, women (W) with acute coronary syndrome (ACS) have worse outcomes compared with men (M). This fact may occur due to gender-specific differences in the presentation and management of patients (P), which were mainly observed in studies dealing with ST-segment elevation infarction (STEMI). There seems to be a gap of knowledge in gender-specific differences in non- ST elevation myocardial infarction (NSTEMI) and unstable angina (UA). Purpose: Assess gender-specific differences in presentation, treatment and outcomes in NSTEMI and UA patients. Methods: A retrospective cohort study from consecutive ACS patients enrolled in a multicentre national registry from October 2010 to December 2018 was conducted, identifying 11394 P admitted with NSTEMI or UA. Demographic, clinical and treatment variables were compared between male gender and female gender P. A Cox multivariate regression was performed to evaluate predictor factors of stablished endpoints: mortality at 1-year (1y) and cardiovascular (CV) hospitalization at 1-year. Results: A total 11394 P were included, 8145 M (71.5%) and 3249 W (28.5%), mean age of 68±13. W, comparing with M, had higher age (72±12 vs 66±13, p=0.001), higher prevalence of hypertension (85% vs 72%, p=0.001) and diabetes (41% vs 34%, p=0.001) and longer time from symptoms to hospital admission (360 minutes vs 297 minutes, p=0.001). Chest pain was less frequent as first symptom in W (85.6% vs 91.3%, p=0.001). In medical treatment, W had higher chance of not having administration of a loading dose of P2Y12 inhibitor (22.1% vs 18.1, p=0.001) and of being medicated with clopidogrel (85.7% vs 82.1%, p=0.002). At discharge, W were less frequently medicated with an angiotensin-converting enzyme (ACE) inhibitor or an angiotensin II receptor blocker (82.6% vs 84.4, p=0.028). Coronary angiography was less frequently performed in W (77.3% vs 85.7%, p=0.001). Coronary artery disease was less frequently found in the female gender (12.4% vs 4.8%, p=0.001). In-hospital mortality was higher in W (2.9% vs 2.1%), but in the multivariate analysis the female gender was not an independent predictor of in-hospital mortality (OR 1.05 [0.67- 1.65], p=0.823). 1-year mortality was higher in W (9.2% vs 7.3%) and 1-year CV hospitalization was higher in M (16.8% vs 14.4%). After adjusting for covariates in Cox regression analysis, difference was still significant for mortality (HR= 1.274 [1.038 - 1.564], p=0.02) and hospitalization (HR = 0.852 [0.726- 0.998], p=0.047). Conclusion: In this NSTEMI and UA cohort, there are important gender-specific differences in comorbidities, diagnosis, management and outcomes. Gender was an independent predictor of 1-year mortality and 1-year CV hospitalization, but not an independent predictor for in-hospital mortality. Funding Acknowledgement: Type of funding source: None